Levels of Anxiety in Students Level 3 DIII Nursing in Facing Competence Test - Tri Yuniarti Soerono; Rina Tri Handayani; Annisa Andriyani Kardiyanto (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Competency tests need to be held for each student who has completed the level of education that is passed as a form of quality assurance for graduates of health tertiary education and the competency of health workers in Indonesia. Graduation Competency Test is one of the requirements for graduation in Higher Education. The implementation of the competency test is of particular concern because if it does not pass the Nursing DIII students cannot participate in graduation and will not be registered to become prospective nurses. Research Objectives to determine the level of anxiety of third-level students in the Nursing Study Program of STIKES Mamba’ul ‘Ulum Surakarta in facing Competency Test. This research is a descriptive study with the population is all level 3 students of Nursing Diploma Program in 78 students. Data collection tool in the form of a questionnaire from question items in the Hamilton Anxiety Rating Scale (HARS). Total population of 78 students with a total sampling of 78 students. Grade 3 students who did not experience anxiety as many as 4 people (5.1%), mild anxiety as many as 49 people (62.8%), moderate anxiety as many as 11 people (14.1%) and who experienced severe anxiety as many as 14 people (17.9). These results are the percentage of level 3 students have mild anxiety. Level 3 did not experience anxiety by 4 people (5.1%), mild anxiety by 49 people (62.8%), moderate anxiety by 11 people (14.1%) and those who experienced severe anxiety by 14 people (17.9).